AN OVERVIEW OF URBAN SLUM GROWTH AND ENVIRONMENTAL DETERIORATION ON BULBULA AREA OF IBRAHIM KATSINA WARD, JOS, PLATEAU STATE - OREWERE, EMMAMOGE; MARTINS, RUTH RAKIYA; EDOM, ATOMEN (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The Sustainable Development Goals adopted by the United Nation on the provision of clean water and sanitation (goal six) and sustainable cities and communities development (goal eleven) targeted for year 2030 and Nigeria’s Vision 20:2020 Economic Transformation Blueprint cannot be overemphasized. The study is aimed at reviewing the growth of slums and environmental deterioration on Bulbula Area of Ibrahim Katsina Ward Jos, Plateau State. Its objectives are to identify the causes of slum growth and its negative effect on the landscape and find out strategies for solving the problem of environmental deterioration in slum communities. The methodology employed for this study is physical observation, oral interview and the review of related literature. Purposive random sampling technique was used to identify 40 houses under the study area. The study recommends that slum upgrading; planning and implementation should be inclusive of the input of urban designers working closely with slum dwellers, governments and other relevant stakeholders to ensure that prevalence of slums are reduced to the barest minimum and sustainable development is ensured. Keywords: